Factors Associated with Adolescent Sexual Behavior at SMP Muhammadiyah 1 Makassar - passe, Rosita ros; Saleh, Syamsuryanita; Ikawati, Nurul (Poltekkes Kemenkes Maluku, 2025)
Unhealthy sexual behavior among adolescents, especially unmarried adolescents, tends to increase. Although sexual behavior and expression of sexuality are normal phenomena, the context in which sexual behavior is expressed can make behavior abnormal or risky. This study uses an analytical observational method with a Cross Sectional Study approach. The population in this study was the total number of students at SMP Muhammadiyah 1 Makassar, totaling 114 students. The sample in this study was part of the total number of students, namely 30 samples. The sampling technique used the Purposive Sampling technique. Data analysis was processed using SPSS using the Chi-Square statistical test. The results of this study showed that there was a relationship between Knowledge, Parental Roles and Information Sources on Adolescent Sexual Behavior with a ρ-value (0.001)> α (0.05).